Antiadipogenic Effects of Mixtures of Cornus officinalis and Ribes fasciculatum Extracts on 3T3-L1 Preadipocytes and High-Fat Diet-Induced Mice - Park, Eunkuk (Molecules, 2020)
Medicinal plants have been used worldwide as primary alternative healthcare supplements. Cornus officinalis (CO) and Ribes fasciculatum (RF) are traditional medicinal plants applied in East Asia to treat human diseases such as hepatitis, osteoporosis, oxidative stress and allergy. The aim of this study was to examine the anti-obesity effect of CO and RF on preadipocyte 3T3-L1 cells in vitro and high-fat diet (HFD)-induced obesity mice in vivo. Combination treatment of CO and RF in differentiated 3T3-L1 cells inhibited adipocyte differentiation through downregulation of adipogenesis-associated genes such as CCAAT/enhancer-binding protein alpha (Cebpa), fatty acid binding protein 4 (Fabp4), peroxisome proliferator-activated receptor gamma (Pparg) and sterol regulatory element binding protein (Srebp1). In vivo animal models showed that a mixture of CO and RF inhibited HFD-induced weight gain, resulting in decreased abdominal visceral fat tissues and fatty hepatocyte deposition. In addition, CO+RF treatment decreased HFD-induced adipogenesis-associated genes in abdominal white fat tissue. These results suggest that administration of a CO and RF mixture prevented adipocyte differentiation and lipid accumulation in preadipocyte cells and HFD-induced body weight in obesity mice. Therefore, combined therapy of CO and RF may be a protective therapeutic agent against obesity.